Home nursing care for patients with rheumatoid arthritis: educational practices (Research, Society and Development, 2021)
This study aims to search the literature for the activities performed by the nursing team at home to promote a better quality of life for the person with rheumatoid arthritis, emphasizing the importance of health education.  This is an integrative review study.  The search occurred in the databases: LILACS; BDENF and in the SciELO portal.  The descriptors “rheumatoid arthritis were used; Home nursing; Health education.”, selected from the list of Health Sciences Descriptors (DeCS), and crossed with the Boolean operator “AND” and “or”.  The survey took place from June to July 2021.  After the inclusion and exclusion criteria were applied, there were 7 studies used in the research.  Nursing care the person with rheumatoid arthritis at home, was pointed out to be of extreme importance, developing educational actions, care and encouragement to self-care, activities that were effective as an essential factor for the patient's positive prognosis.  It is concluded that the study is relevant as it provides to know the activities performed by the nursing team at home, presenting concepts and actions in all dimensions of care, and thus stimulates the production of new studies about the subject, aiming at future educational and care actions to be more effective and present at home.